2020
DOI: 10.1590/s2175-97902019000418070
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design approach for development of novel microemulsion system and immediate release self microemulsifying tablet of nebivolol HCl

Abstract: The objective of this study was to determine specific combination of pharmaceutical excipients that lead to formulation of efficient nebivolol hydrochloride SMEDDS and its subsequent formulation into IR-SET (Immediate release-Self emulsifying tablet) which will enhance its solubility and dissolution. Solubility and Pseudo-ternary phase studies were carried out to identify the excipients showing highest solubility and to identify the zone of microemulsion with selected ingredients. Liquid-SMEDDS (L-SMEDDS) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…4 A depicts the differential scanning calorimetry (DSC) thermograms for NBV, Span, Labrasol, their PM, and the selected SNVs either plain or medicated. NBV thermogram showed a single sharp endothermic peak at 226.52 °C ( Trivedi et al, 2020 ). The drug's crystalline structure was revealed by its distinct peak and it corresponded to its melting point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A depicts the differential scanning calorimetry (DSC) thermograms for NBV, Span, Labrasol, their PM, and the selected SNVs either plain or medicated. NBV thermogram showed a single sharp endothermic peak at 226.52 °C ( Trivedi et al, 2020 ). The drug's crystalline structure was revealed by its distinct peak and it corresponded to its melting point.…”
Section: Resultsmentioning
confidence: 99%
“…5 displays the release profile of NBV from a control suspension and the optimized three formulae (F1, F4, and F14). It was obvious that incorporating NBV within SNVs significantly slowed down the drug release as the vesicular system is well-known to act as a reservoir that slowly releases the drug providing a sustained release profile ( Trivedi et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2A. Literature study showed that the oil having the maximal solubilizing potential will be selected to achieve optimum drug loading 24 .…”
Section: Comparison Of % Permeation Profile Of Optimized Microemulsio...mentioning
confidence: 99%
“…The lipids are likely to augment the lymphatic transport of a lipophilic drug substance leading to enhanced oral bioavailability [8][9][10][11] . The drug, i.e., nebivolol, chosen in the present study is a BCS class II highly selective thirdgeneration β 1 -receptor antagonist, an antihypertensive drug with poor water-solubility and high permeability (log P of 4.03) undergoes rapid first-pass metabolism caused by cytochrome P450 2D6 (CYP2D6) enzymes resulted in poor bioavailability (12%) 12 . All these considerations have led to the development of solid oral SMEDDS.…”
Section: Introductionmentioning
confidence: 99%